Biochemical relevance of Cr(III) complexes of isoniazid: synthesis, characterization, DFT, antibacterial screening, antioxidant activity and glucose-lowering effect in STZ-induced diabetic rats. Issue 4 (16th February 2019) - Shukla, Satyendra N.; Gaur, Pratiksha; Jhariya, Sangeeta; Chaurasia, Bhaskar; Vaidya, Preeti; Azam, Mohammad
Abstract: Molecular mechanism suggests that the incorporation of an antioxidant organic moiety to chromium will be a sound strategy for the synthesis of safer and more effective hypoglycemic compounds. Two Schiff base ligands were derived by condensation of isonicotinyl hydrazide with salicylaldehyde/ o -hydroxyacetophenone which further yield four novel chromium(III) complexes of types [Cr(L)Cl2 (H2 O)] and [Cr(L)2 ]Cl. The ligands and complexes were characterized by analytical and spectroscopic techniques. DFT study at the basic set B3LYP and TD-SCF/6-311-G level was employed to confirm the geometry of the investigated compounds. Ligands were tested for their antioxidant activity and exhibited good antioxidant activity. Assessment of insulin-like activity of the complexes was initially performed in vitro by measuring the inhibition of α-amylase. The complex with highest in vitro activity was investigated for in vivo antidiabetic activity on the model of STZ-induced diabetic rats, which demonstrated that complex4 significantly lowers the blood glucose level in rats. Toxicity level and antioxidant activity of the complex were also tested, which exhibit good tolerance level and antioxidant activity. Histological analysis of the pancreas of animals under investigation reveals the good condition of the pancreas treated with the complex. Ligands and complexes were also tested for antibacterial activity against Escherichia coli .